Clinical profile of dengue fever infection in King Abdul Aziz University Hospital Saudi Arabia - Maimoona M Ahmed (Journal of Infection in Developing Countries)
Background: The study aimed to compare the clinical profile of all patients diagnosed with dengue viral infection at King Abdul Aziz University Hospital (KAAUH), during 2005-2008.